(untitled) (Eurasian Research Bulletin, 2025)
This article traces the development of translation theory from its origins in classical antiquity, through the Middle Ages and the Renaissance, to the modern era. It also examines key theoretical models, including transformational, semantic-semiotic, situational, and communicative approaches, and explores the dual linguistic and nonlinguistic aspects of translation.